Design and Construction of a Website-Based E-Commerce Application for Bamboo Crafts for Belega Village, Gianyar Regency - Dicky Umardhani; Putu Wira Buana; Fajar Purnama (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
The development of information and communication technology in Indonesia has grown significantly over the past few years. Thus, there are many opportunities to digitize the business process of a business or business ecosystem. One of them is in the field of digital economy by adapting business processes into a digital platform, such as designing an e-commerce platform in a village that has commodities in it so that related commodities can increase the visibility of their products. This research uses Belega Village as a case study location considering that this village has a commodity in the form of bamboo crafts. Research was conducted to build a web-based bamboo handicraft e-commerce application that would be expected to increase product visibility. The application itself is built using the Agile Development method using the sprint model. This application is built with a microservice architecture with Express.js technology as a backend service and Next.js to create client applications and PostgreSQL as a DBMS. The result of this research is a web-based e-commerce application that is expected to increase the visibility of products from bamboo crafts from Belega Village.